Analisis Potensi Bahaya pada Kalibrasi Metering System Menggunakan Metode JSA - Fida Husnaseptia; Andivas, Marulan; Misrianto, Misrianto; Harits, Dimaz (Fakultas Teknik UMRI, 2024)
The oil and gas industry carries high operational risks, particularly in metering system calibration activities. This research uses the Job Safety Analysis (JSA) method to find and examine possible risks in PT. X's metering system calibration procedure. Direct observation, conversations with engineers and HSE teams, and an examination of pertinent papers were used to gather data. Risk analysis was performed using a semi-quantitative approach by assessing the likelihood and severity levels for each identified potential hazard. The research identified 12 potential risks distributed across three categories: low risk (25%), medium risk (66.67%), and high risk (8.33%). The highest risk was found in the power transmitter isolation phase with electrocution hazard. Based on these findings, risk control recommendations are formulated which include training and certification, procedures, engineering controls and proper use of PPE. The implementation of comprehensive and systematic risk control is key to ensuring work safety and the extinction of company operations.